Midnight Crossroad : Midnight, Texas #1 - Harris, Charlaine; Bennett, Susan; Recorded Books, LLC. (Prince Frederick, MD : Recorded Books, 2014)
Welcome to Midnight, Texas, a town with many boarded-up windows and few full-time inhabitants, located at the crossing of Witch Light Road and Davy Road. It's a pretty standard dried-up western town. There's a pawnshop (someone lives in the basement and is seen only at night). There's a diner (people who are just passing through tend not to linger). And there's new resident Manfred Bernardo, who thinks he's found the perfect place to work in private (and who has secrets of his own). Stop at the one traffic light in town, and everything looks normal. Stay awhile, and learn the truth.
Title from container.
Compact disc.
In container (17 cm.).
"With tracks every 3 minutes for easy book marking"--Container.
Narrated by Susan Bennett.
Keywords: Young women -- Fiction; Texas -- Fiction; Fantasy fiction; Audiobooks